SCURVY - A FORGOTTEN DISEASE UNDER THE GUISE OF HEMORRHAGIC VASCULITIS - N. S. Chipigina; N. Yu. Karpova; M. A. Bolshakova; T. Y. Kalinina; E. D. Askhabova; L. M. Yuzakharova; S. D. Bagmanyan; K. A. Badalyan; O. K. Yutsevich (SINAPS LLC, 2017)
Background. Scurvy is very rarely seen in modern conditions. Material and Methods. We observed a case of scurvy that occurred as a result of prolonged malnutrition in a previously healthy 50-year-old man with low income. Results. The disease was manifested by severe weakness, edema of the legs, gingivitis and spontaneous hemorrhagic eruptions on the legs, which were initially regarded as hemorrhagic vasculitis. The confluent character of hemorrhagic eruptions, their predominant localization along the posterior surface of the legs, the presence of perifollicular hemorrhages, pathognomonic for scurvy, gingivitis, complete absence of ascorbic acid consumption for several months, as well as concomitant alimentary dystrophy and multivitamin deficiency, allowed us to suspect scurvy in the patient. The rapid effect of vitamin C treatment has confirmed this diagnosis. Conclusions. The differential diagnosis of spontaneous hemorrhagic eruptions and purpura in patients with prolonged malnutrition should include scurvy, a disease almost forgotten in modern conditions.